2016
DOI: 10.1007/s13744-016-0441-7
|View full text |Cite
|
Sign up to set email alerts
|

Plant Resistance to the Moth Tuta absoluta (Meyrick) (Lepidoptera:Gelechiidae) in Tomato Cultivars

Abstract: The resistance of 11 tomato cultivars (Ps-6515, Berlina, Poolad, Petoprid-5, Zaman, Matin, Golsar, Sandokan-F1, Golshan-616, Sadeen-95 and Sadeen-21) to the tomato moth, Tuta absoluta (Meyrick) (Lepidoptera:Gelechiidae) was investigated under field conditions. A randomized complete block design was used with three replications. Data analysis indicated that there were significant differences (P < 0.05) among cultivars regarding leaflet damage, leaf damage, overall plant damage, number of mines per leaf, number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Similar results to those obtained in this study were reported by Maciel et al (2011) and Dias et al (2013), who observed lower oviposition and number of T. absoluta larvae in tomato genotypes with higher acylsugar content. Sohrabi et al (2017) attributed the resistance of tomato cultivars Berlina, Zaman and Golsar to T. absoluta to the high density of foliar trichomes. Lucatti et al (2013) and Andrade et al (2017) associated the lowest amount of egg and nymph and consequently the resistance of the tomato accessions evaluated to Bemisia tabaci with the highest amount of type IV trichomes.…”
Section: Id Genotypementioning
confidence: 99%
“…Similar results to those obtained in this study were reported by Maciel et al (2011) and Dias et al (2013), who observed lower oviposition and number of T. absoluta larvae in tomato genotypes with higher acylsugar content. Sohrabi et al (2017) attributed the resistance of tomato cultivars Berlina, Zaman and Golsar to T. absoluta to the high density of foliar trichomes. Lucatti et al (2013) and Andrade et al (2017) associated the lowest amount of egg and nymph and consequently the resistance of the tomato accessions evaluated to Bemisia tabaci with the highest amount of type IV trichomes.…”
Section: Id Genotypementioning
confidence: 99%
“…Based on a variety of life parameters, we concluded that the Korral cultivar was relatively resistant to T. absoluta, whereas the Valouro cultivar was relatively susceptible to this pest. In line with these results, many studies have reported that the life parameters of and damage caused by T. absoluta vary significantly when the pest is reared on different tomato cultivars, and that these variations may arise from differences in the quality and quantity of nutrients, phagostimulant factors, trichome density, and the abundance of secondary metabolites among cultivars (Pereyra & Sanchez 2006;Proffit et al 2011;de Oliveira et al 2012;Sohrabi et al 2016b;Ghaderi et al 2017). For example, at least three types of secondary metabolites, namely acyl sugars, zingiberene, and 2-tridecanone, are known in association with tomato resistance to T. absoluta (Maluf et al 2010;de Oliveira et al 2012).…”
Section: Discussionmentioning
confidence: 61%
“…These metabolites have been reported to negatively affect the colonization and the intrinsic rate of population increase in diverse arthropod species (Oriani & Vendramim 2010;de Oliveira et al 2012). Some recent studies have argued that tomato cultivars significantly differ in their susceptibility to T. absoluta (Oliveira et al 2009;de Oliveira et al 2012;Sohrabi et al 2016b;Ghaderi et al 2017), and that resistance to the pest is positively associated with the density of trichomes and the content of secondary metabolites (Proffit et al 2011;de Oliveira et al 2012;Sohrabi et al 2016b). For example, ovipositing females of T. absoluta are able to discriminate tomato cultivars according to their volatile profile and prefer specific cultivars that are more suitable as food for their larvae (Proffit et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Host plant resistance to insects is an alternative method to reduce pesticide use and the problems facing in a pest management system (Panda and Khush, 1995; Maluf et al ., 2010). Resistance of different tomato cultivars to T. absoluta in greenhouses and open fields were reported in previous studies (Gilardón et al ., 2001; Leite et al ., 2001; Sobreria et al ., 2009; Gharekhani and Salek-Ebrahimi, 2014; Sohrabi et al ., 2016, 2017). On the contrary, several species of natural enemies have been found to be in association with T. absoluta which among them, Trichogramma parasitoids were considered as one of the most effective biological agents for the management of the pest (Cabello et al ., 2009; Desneux et al ., 2010; Cherif and Lebdi-Grissa, 2013).…”
Section: Introductionmentioning
confidence: 99%